Parametric down conversion process in one dimensional-photonic band gap structure - Wicharn, S.; Buranasiri, P. (My University, 2012)
In this paper we have numerically investigated the parametric down conversion process in one dimensional-photonic band gap (1D-PBG) structure, which is composed of linear and nonlinear dielectric layers, under four wave mixing phenomena. The nonlinear dielectric layer is material with third-order nonlinear susceptibility χ (3). First, we used coupled-mode theory and slowly varying amplitude approximation to derive a complete set of nonlinear coupled mode equations (NLCMEs) for the FWM phenomena. Then, we have solved these NLCMEs by using undepleted pump approximation. We have got the solution for amplitude of signal and idler waves. Finally, we have used these solutions to calculate the down-converted frequency conversion efficiency. We found that the conversion efficiency can be enhanced by increasing the number of periodic layers and χ (3) value. Meanwhile, the conversion efficiency is decreased by increasing of phase mismatch (Δk). © 2012 SPIE.
Keywords: Four wave mixing; Nonlinear frequency conversion efficiency; Parametric down-conversion process; Photonic band gap structures; Photonic crystals